Bio-efficacy Studies of Unique in Relation to Growth, Yield and Shelf Life of Super Sonaka Grape Variety Grown in Sangli Region of Maharashtra - , R. G. Somkuwar, Sadashiv Landage, P. S. Gharate, P. S. Karande, P. B. Kakade (Archives of Current Research International, 2025)
The effect of Unique (bio-stimulant) was studied on yield and quality of Super Sonaka, elongated grape variety by applying different doses through foliar sprays (20, 25 and 30 ml/L) at five key stages of growth (12-13 days after fruit-pruning, 23-25 days after fruit-pruning, at 75-100% flowering, at 100% fruit set (2 mm berry size) and 8-10 days after fruit set). Among the different treatments, the foliar application of 30 ml/L significantly improved several growth and yield parameters including leaf area (163.1 cm²), average bunch weight (580.5 g), 50-berry weight (200.18 g), berry length (28.4 mm), berry diameter (17.2 mm) and yield (20.92 kg/vine) respectively. Biochemical attributes like phenol content (0.54 mg/g), protein (14.9 mg/g), reducing sugar (297.3 mg/g), calcium (48.9 ppm) and phosphorus (0.315%) were also improved with reduction of post-harvest loss (PLW) upto 5.2%. Additionally, the pedicel and skin thickness increased to 0.560 mm and 0.186 mm, respectively. Therefore, the foliar application of 30 ml/L of Unique at these five stages is recommended to optimize both the quality and yield of Super Sonaka grapes.